THE ELECTION CAMPAIGN OF THE POLITICAL PARTIES UNDER THAI CONSTITUTION B.E 2560 : CASE STUDY OF THE GENERAL ELECTION ON THE 24TH OF APRIL B.E.2562 - Nantavaropas, Nantana; Sangpong, Rahat (Journal of MCU Social Science Review, 2019)
The general election held on the 24th of April 2019 transformed Thailand’s history in many ways. First, the rules governing the election were completely different from preceding elections. Second, the number of candidates and parties that participated in this election was the highest in the nation’s history. Third, the results of the aforementioned election were not as most predicted. These astonishing features of the 2019 election inspired this piece of research as it aims to understand the campaigning strategies of the three most successful parties which are the Phue Thai, Palang Pracharat, and Anarkoth Mai (Future Forward) parties using Bruce I. Newman’s Political Marketing Theory. The synthesis of this study revealed three new ideas that will contribute to the existing body of literature: 1) In this election, if many parties made use of political marketing concepts, the deciding factor would be a party’s superior policy platform and that platform’s probability of being realized. 2) The political context was an important deciding factor in this election. 3) According to the Political Marketing Theory, parties that offers a novel policy platform that are distinct from those of other parties will often be victorious.